2021
DOI: 10.31219/osf.io/7u48z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative and Qualitative 1H, 13C, and 15N NMR Spectroscopic Investigation of the Urea–formaldehyde Resin Synthesis

Abstract: Urea-formaldehyde resins are bulk products of the chemical industry. Their synthesis involves a complex reaction network. The present work contributes to its elucidation by presenting results from detailed NMR spectroscopic studies with different methods. Besides 1H NMR and 13C NMR also 15N NMR spectroscopy is applied. 15N-enriched urea was used for the investigations. A detailed NMR signal assignment and a model of the reaction network of the hydroxymethylation step of the synthesis are presented. Due to its … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Using the first initial F/U mole ratio of 3.0 resulted in shorter gelation time and lower free-formaldehyde of UF resins than those prepared with the first initial F/U of 2.0 and 4.0. It is known that one molecule of urea can react with three molecules of formaldehyde to form hydroxymethyl ureas, and then undergoes condensation reaction to form methylene linkages and ether linkages (Kibrik et al, 2014;Steinhof et al, 2014). This yielded in less free-formaldehyde in the UF resins system, and eventually increased the non-volatile solids content and viscosity of resins.…”
Section: Basic Properties Of Uf Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the first initial F/U mole ratio of 3.0 resulted in shorter gelation time and lower free-formaldehyde of UF resins than those prepared with the first initial F/U of 2.0 and 4.0. It is known that one molecule of urea can react with three molecules of formaldehyde to form hydroxymethyl ureas, and then undergoes condensation reaction to form methylene linkages and ether linkages (Kibrik et al, 2014;Steinhof et al, 2014). This yielded in less free-formaldehyde in the UF resins system, and eventually increased the non-volatile solids content and viscosity of resins.…”
Section: Basic Properties Of Uf Resinsmentioning
confidence: 99%
“…This indicated that UF resins prepared using the second initial molar ratio of 2.0 were linear structures, while using the second initial molar ratio of 1.7 produced branched structures of UF resins. As mentioned above, one molecule of urea can react with three molecules of formaldehyde to form hydroxymethyl ureas, and then methylene linkages, and ether linkages (Kibrik et al, 2014;Steinhof et al, 2014). Therefore, by using a combination of the first initial F/U mole ratio of 3.0 and 4.0 and second initial F/U mole ratio of 1.7, the resulting resins were superior in properties compared to the conventional initial molar ratio of 2.0.…”
Section: Basic Properties Of Uf Resinsmentioning
confidence: 99%